Investigating the association between blood cobalt and gallstones: a cross-sectional study utilizing NHANES data - Yunfan Li; He Han; Kuanxuan You; Chaojun Ma; Xin Fan (Frontiers Media S.A., 2024)
BackgroundWith the use of cobalt alloys in medical prosthetics, the risk of cobalt exposure has increased. The objective of this study was to investigate the correlation between blood cobalt levels and the occurrence of gallstones utilizing data from the National Health and Nutrition Examination Survey (NHANES).MethodsData collected between 2017 and 2020 were analyzed, encompassing a total of 5,610 participants. Cobalt concentrations in whole blood specimens were directly measured using inductively coupled plasma mass spectrometry (ICP-MS). The presence of gallstones was ascertained through a standardized questionnaire. To assess the association between blood cobalt levels and the presence of gallstones, logistic regression analysis, restricted cubic spline analysis, and subgroup analysis were utilized.ResultsThe results of logistic regression analysis revealed a heightened risk of developing gallstones in the Quartiles 2 and Quartiles 4 groups based on blood cobalt levels when compared to the Quartiles 1 group (OR = 1.54, 95% CI: 1.15-2.07; OR = 1.35, 95% CI: 1.03-1.77). The restricted cubic spline analysis exhibited a positive linear correlation between blood cobalt levels and the occurrence of gallstones. Subgroup analyses further demonstrated a statistically significant correlation between the Quartiles 4 category of blood cobalt levels and an elevated risk of gallstones, particularly among individuals aged 60 years or older, females, those with a body mass index (BMI) equal to or exceeding 25, serum total cholesterol levels below 200 mg/dL, as well as individuals diagnosed with hypertension or diabetes.ConclusionOur study findings indicate a notable association between elevated blood cobalt levels and an increased risk of gallstones. To establish a causal relationship between blood cobalt levels and the elevated risk of developing gallstones, further prospective cohort studies are warranted.